Laryngopharyngeal Reflux Is a Potential Risk Factor for Juvenile-Onset Recurrent Respiratory Papillomatosis - Formánek, Martin; Komínek, Pavel; Jančatová, Debora; Staníková, Lucia; Tomanová, Radoslava; Vaculová, Jana; Urík, Milan; Šlapák, Ivo; Zeleník, Karol (BioMed research international, 2019)
Introduction: Human papillomavirus (HPV) causes juvenile-onset recurrent respiratory papillomatosis (JORRP). Although HPV is common in children, the prevalence of JORRP is low. It is likely that other factors contribute to the pathogenesis of JORRP, during either activation or reactivation of a latent HPV infection. There is evidence that laryngopharyngeal reflux (LPR) might be such a risk factor for adult-onset recurrent respiratory papillomatosis. This study investigated if LPR might also be a risk factor for JORRP. Materials and Methods: Children with JORRP of the larynx that required microlaryngoscopy at a tertiary referral hospital were included in this prospective case-series study from November 2015 to November 2017. Using immunohistochemistry, HPV infection and pepsin associated with LPR were diagnosed from laryngeal biopsies. Results: Eleven children (aged 4-14 years) were analyzed. No patient had a history of immunodeficiency or tobacco smoke exposure. All patients underwent at least three previous surgeries due to JORRP and had been vaccinated against HPV in the past. Five children were treated using antivirotics and immunomodulators. The only known maternal risk factor was that three mothers were primiparous. All 11 samples were infected with HPV (type 6 or 11). Pathologic LPR was diagnosed in 5/11 children (45.5%). Conclusion: LPR may be a risk factor for JORRP, contributing to its development by activating or reactivating a latent HPV infection. Results are in accordance with those from our previous study in adults.
Keywords: infekce dýchací soustavy; dospělí; Female; Papillomavirus Infections; dítě; předškolní dítě; Adult; ženské pohlaví; biopsie; Adolescent; Papillomaviridae; lidé; hypofarynx; Respiratory Tract Infections; Risk Factors; Male; Biopsy; Child, Preschool; Laryngopharyngeal Reflux; infekce papilomavirem; rizikové faktory; laryngofaryngeální reflux; Child; mužské pohlaví; Hypopharynx; mladiství; Humans